Impact of external shading strategy on energy performance of multi-story hotel building in hot-humid climate. (15th February 2019) - Alhuwayil, Waleed Khalid; Abdul Mujeebu, Muhammad; Algarny, Ali Mohammed M.
Abstract: Passive design strategies are the most feasible and economic ways of energy and thermal management in buildings, if appropriately incorporated at the conceptual design stage. Though many works have been reported on the application of external shading options, a shading strategy that incorporates the features of both external shading devices and self-shading envelope, is yet to be explored. The present study was focused on the energy saving potential and economics of incorporating external shading devices with self-shading envelope for a multi-story hotel building in hot-humid climate of Saudi Arabia. The modeling and the energy simulations were performed by DesignBuilder (Version 4.5.0.148). According to the base-design geometry of the building, appropriate shading options were proposed for the north, south, north-east, north-west, south-east and south-west facades. External walls and roof were insulated with fiber glass and windows were double-glazed (DG), in compliance with the Saudi Building Code - 601. The shading strategy was chosen in such a way that it forms part of a self-shading envelope while improving energy performance and contributing additional space at very affordable cost. The results show that the proposed shading could save the annual energy consumption of the building by 20.5% compared to the base case. The payback period for the additional investment required for incorporating the passive shading strategy is estimated to be 2 years. Study of another option by improving the baseline insulation and glazing (with polyurethane in walls and roof and triple low-e glazed shows, without shading) shows that it saves only 5% of annual energy consumption, and the payback period is unacceptably long (84 years). Highlights: Effect of shading strategy on energy performance of multi-story hotel building. The shading strategy combines shading devices and self-shading envelope. The proposed shading configuration could save 20.5% of annual energy consumption. The additional cost for the shading can be recovered in 2 years.